TINJAUAN PELAKSANAAN PENGODEAN DIAGNOSIS PENYAKIT PADA PASIEN RAWAT JALAN DI RSUD TUGUREJO PROVINSI JAWA TENGAH - Qisthi Qurrota A’yuni; Kori Puspita Ningsih (MEDIA ILMU KESEHATAN, 2017)
Background: The implementation of diagnosis coding in the Medical Record Unit at a health institution plays an important role in the administration of medical records at the hospital because it describes the quality management of medical records. In order to maintain the quality, it is crucial to accomplish the accreditation standard, especially at ICM. 13 related coding. Objective: This study aimed to understand the procedures of implementation, compliance disease diagnosis code execution in an outpatient based on accreditation standards KARS 2012, the percentage and the resistance of diagnosis coding implementation in outpatients. Methods: This research was a descriptive qualitative approach with cross sectional design. The subjects were medical records staff with Diploma 3 medical record education background, outpatients coding officer, reporting coordinator, the head of clinic space and a clinic nurse. The data collectin techniques used were observation, documentation and interview studies. Testing the validity of the data use triangulate of source and triangulate of techniq. Results: The coding was done by the medical records staffs and nurses, coding reference were in the form of policies, guidelines and standard operating procedure, guidelines used by nurses in coding was assistive book. Tugurejo Hospital Accreditation in Central Java province had fulfilled the five elements of ICM. 13 and passed the accreditation of type B-level plenary meeting. The percentage of outpatient coding implementation reached 78.6%, consisting of JKN amounted to 75.4% and 3.2% were non JKN. The barriers of coding implementation consists of five elements such as man, method, material, machine and money. Conclusion: In general the implementation of the coding in JKN outpatient has already done optimally, but for non JKN has not been optimal because of the inhibiting factors such as man, method, material, machine and money. Keywords: Coding, disease diagnosis, outpatient